Tingkat Life Skills Siswa pada Ekstrakurikuler Futsal - Budiman Budiman; Fitria Marfianti; Erick Burhaein (Journal on Education, 2023)
This study aims to determine the level of life skills of students after participating in futsal extracurricular activities. The method used is descriptive with a survey approach. The population in this study was all students of SMK Negeri 9 Garut who participated in futsal extracurricular activities. The sample obtained was 50 respondents, sampling using the total sampling technique. The instrument used by the life skills questionnaire compiled by researchers consists of six components, namely intrapersonal (focus, goal setting, emotional regulation) and interpersonal (honesty, teamwork, respect) Data analysis using descriptive analysis as outlined in the form of percentages. The results showed that the level of life skills of students after participating in futsal extracurricular activities was in the category of "less" by 34%, "enough" by 48%, and "good" by 18%.